COMMON-POOL RESOURCES WITH FREE MOBILITY. - DORJ, DOLGORSUREN (Economic Inquiry, 2013)
The Tragedy of the Commons may get worse if people freely move between different commons. We conducted laboratory experiments with the common-pool resource setting in which people freely moved between two localities. The localities differed by governing regimes: no regulation or sanctions imposed either exogenously or chosen by majority voting. We find that under free mobility, efficient resource use is attainable with sanctions given that the target harvesting level adjusts to the number of users. People self-select into different regimes based on their behavioral types. Results are consistent across the United States and Mongolia. ( JEL C7, C72, C91, Q2, R12)